2020
DOI: 10.1123/japa.2019-0217
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of Occupational Therapy Interventions to Address Sedentary Behavior and Pain Among Older Adults

Abstract: This study aimed to determine the feasibility of an occupational therapy intervention to address sedentary behavior and pain among older adults residing in assisted living facilities. A single group pretest and posttest design was implemented using the Sedentary Behavior Questionnaire, actigraphy technology, and daily activity logs to measure sedentary behavior. The Short-Form McGill Pain Questionnaire was used to assess pain. Occupational therapy intervention focused on individualized goals related to partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…By contrast, no significant changes in pain level were observed in the other countries, where the population was younger. It is well known that musculoskeletal pain is frequently associated or triggered by psychological stressors [58] or sedentary behaviors [59,60] commonly occurring during social isolation. In fact, during quarantine, the population usually spends a longer time in front of television, computers, or smartphones since any type of activity at home is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, no significant changes in pain level were observed in the other countries, where the population was younger. It is well known that musculoskeletal pain is frequently associated or triggered by psychological stressors [58] or sedentary behaviors [59,60] commonly occurring during social isolation. In fact, during quarantine, the population usually spends a longer time in front of television, computers, or smartphones since any type of activity at home is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The sample from Portugal have smoked for fewer years (p < 0.05), however, they have the youngest sample. 60,470,911 680 11.2 France ysis, 141 participants were excluded (4.2%) from the initial respondents because they were from different countries or with ages below 18 years old, thus leaving a total of 3194 questionnaires to be analyzed. The included answers per country and the respective correspondence per millions of inhabitants are indicated in Table 1.…”
Section: Sociodemographic Characteristics and Sample Health Conditionmentioning
confidence: 99%
“…Multiple studies have shown the benefits of physical and occupational therapy in the older adult population, especially for chronic back and joint pain [35][36][37]. One study evaluated the barriers to physical therapy in treating knee pain in older adults and found that despite therapeutic alliance among members of the healthcare team, barriers continued to persist in older adults' Volume 07; Issue 03 Int J Nurs Health Care Res, an open access journal ISSN: 2688-9501 adherence to physical therapy, including changes in or retained knowledge of treatment [39].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
“…There has been limited research focused on interventions to decrease sedentary behavior among AL residents; we are aware of only four previous pilot interventions (Dillon & Prapavessis, 2020; Giné-Garriga et al, 2020; Naber et al, 2020; Voss et al, 2020b). The Voss et al intervention utilized strategies at various levels of the ecological model and was found to be feasible with a trend toward decreased self-reported sedentary behavior but did not decrease device-measured sedentary time (Voss et al, 2020b).…”
Section: Physical Activity and Sedentary Behavior In Assisted Livingmentioning
confidence: 99%
“…The Voss et al intervention utilized strategies at various levels of the ecological model and was found to be feasible with a trend toward decreased self-reported sedentary behavior but did not decrease device-measured sedentary time (Voss et al, 2020b). Naber et al conducted an occupational therapy intervention to decrease sedentary behavior through individualized goal setting (Naber et al, 2020). Residents in that study had a nonsignificant increase in daily step counts but did not decrease self-reported sedentary behavior.…”
Section: Physical Activity and Sedentary Behavior In Assisted Livingmentioning
confidence: 99%